Prototype Aplikasi Sertifikasi Kelayakan Lift Berbasis Website - Fajar Septian; Saipul Anwar (Teknik Informatika, 2019)
Lift as a means of transporting people and goods at a height contains potential hazards and can cause work accidents resulting in material losses, human injury and death. Accident data show the causes of elevator accidents are caused by human error factors in elevator maintenance and maintenance. The object of this research is PT Berca Schindler Lifts, which is engaged in elevator and escalator installation services spread in more than 1,000 branch offices throughout the world. Berca Schindler Lifts provides design, installation, maintenance, maintenance and modernization of transportation systems for each type of building. To satisfy and provide a sense of comfort and safety for consumers or elevator users it is necessary to check the elevator eligibility certification. The feasibility check of the elevator is still using paper checkers and stationery. This study aims to make the application of websitebased elevator eligibility certification as an electronic checklist during the process of checking the feasibility of the elevator by implementing a prototyping development model. This research resulted in a prototype of a website-based elevator eligibility certification application. The results of testing with black-box testing show all the features provided by this application can run according to user needs.